Enrichment of meat products by iodine through the use of seaweed - Kryzhova (Vengliyk), Julia (My University, 2013)
There were developed meat products including burgers, meatballs, rissoles, dumplings, sausages for grilling, which had various heat treatment in order to study the iodine and selenium in finished products and their receipt to the body when consumed products.
Keywords: ковбаски для гриля; водорості; мікроелементи; термічна обробка; колбаски для гриля; водоросли; микроэлементы; термическая обработка; semi sausages for grilling; seaweed; trace elements; heat treatment; кафедра технології м’яса і м’ясних продуктів